Comparison of Structural Response Utilizing Probabilistic Seismic Hazard Analysis and Design Spectral Ground Motion - Pranowo, .; Makrup, Lalu; Pawirodikromo, Widodo; Muntafi, Yunalia (Civil Engineering Journal, 2024)
Indonesia is seismically active due to tectonic plate convergence south of Java Island. In the examination of earthquake-resistant structures, Indonesia possesses the SNI 1726-2019 rule; however, it requires re-evaluation in conjunction with other seismic motions, specifically the PSHA method. The PSHA approach is employed in probability-based seismic hazard analysis, taking into account uncertainties related to earthquake magnitude, location, and frequency to provide a comprehensive assessment of a location's hazard level. To demonstrate the impact of ground motion induced by earthquakes on structural reaction, it is essential to study the structure using the time history of SNI and PSHA artificial earthquake shaking. Spectrum matching with target spectra derived from probabilistic seismic hazard analysis can build artificial time histories. Consequently, the time history obtained from the analysis can be considered to be derived from the probabilistic methodology. Both analytical methods, SNI and PSHA, indicate that the structural reaction of the Alana Hotel is not markedly different, and the structure remains secure against seismic activity. Doi: 10.28991/CEJ-SP2024-010-012 Full Text: PDF